Reply to Garnemark et al. The Swedish National Formulary for Children ePed. Comment on “Shaniv et al. A Callout for International Collaboration. Reply to Giger, E.V.; Tilen, R. Comment on “Shaniv et al. Neonatal Drug Formularies—A Global Scope. Children 2023, 10, 848”. Children 2023, 10, 1803” - Dotan Shaniv; Anne Smits; Karel Allegaert; on behalf of the Neonatal Drug Formularies Group (Children)
We received the comment from our Swedish colleagues and have read it with interest [...]